Down-regulation of CYLD as a trigger for NF-κB activation and a mechanism of apoptotic resistance in hepatocellular carcinoma cells - Urbanik, Toni; Köhler, Bruno Christian; Boger, Regina; Wörns, Marcus Alexander; Heeger, Steffen; Otto, Gerhard; Hövelmeyer, Nadine; Galle, Peter Robert; Schuchmann, Marcus; Waisman, Ari; Schulze-Bergkamen, Henning (International journal of oncology, 2011)
The cylindromatosis gene (CYLD) was identified as a tumor suppressor gene, which is mutated in familial cylindromatosis (Brooke-Spiegler syndrome), an autosomal-dominant predisposition to multiple tumors of the skin appendages. CYLD is a deubiquitinating enzyme acting as a negative regulator of the nuclear factor κB (NF-κB) signaling pathway by removing lysine-63-linked polyubiquitin chains from NF-κB activating proteins. In order to investigate the role of CYLD in apoptotic signaling in human hepatocellular carcinoma (HCC) cells, we first studied the expression levels of CYLD in HCC tissues. CYLD expression was lower in HCC both at protein and mRNA levels compared to the surrounding non-malignant tissue. In order to further study the role of CYLD in the apoptotic sensitivity of HCC cells, CYLD was specifically down-regulated in HCC cell lines via RNA interference. The specific down-regulation of CYLD resulted in increased resistance towards treatment with doxorubicin, 5-fluorouracil and cisplatin. In addition, the down-regulation of CYLD in HCC cells decreased the sensitivity towards tumor necrosis factor-α-induced apoptosis. The CYLD knockdown also led to the degradation of the NF-κB inhibitor, IκB-α, resulting in enhanced NF-κB activity in HCC cells. Finally, we found that CYLD expression was triggered by the multikinase inhibitor, sorafenib, by the inhibition of Raf-1, as well as by the blockage of the pro-survival kinases, MEK (U0126) and the epidermal growth factor receptor (AG1478). In summary, we show that CYLD is down-regulated in human HCC and is involved in the apoptotic resistance of HCC cells. Our data indentify the reconstitution of CYLD expression as an attractive approach for overcoming resistance to treatment in HCC.
Gesehen am 01.12.2022